Predictors of vertical jumping capacity in soccer players - Križaj, J.; Rauter, S.; Vodicar, J.; Hadžic, V.; Šimenko, J. (Isokinetics and Exercise Science, 2019)
BACKGROUND: Vertical jumping capacity is important in modern soccer to gain advantage over opponent during the defensive and offensive activities. Predictors of jumping capacity in soccer players are not well studied. OBJECTIVE: The main aim of our study was to evaluate how isokinetic strength of the thigh muscles is related to jump performance. METHODS: Twenty-five (N = 25) elite soccer players volunteered to participate in the study. Thigh muscle strength (concentric for hamstrings and quadriceps, and eccentric for hamstrings only) was evaluated at 60 ° /sec using an isokinetic dynamometer, while jump capacity was evaluated using a bilateral force plate to measure the jump height of squat (SJ) and countermovement (CMJ) jump. Linear regression model was used to evaluate how well can isokinetic strength parameters (independent predictors) predict jumping capacity in soccer players (dependent variable). RESULTS: In a linear regression model concentric quadriceps strength has significantly explained the vertical jump height, while other parameters (hamstring concentric or eccentric strength) did not reach the significance level (p > 0.05). When left and right concentric quadriceps strength was used the model was statistically significant (F = 4.76, p = 0.02; R square 0.31), but only right concentric quadriceps strength was significant predictor (t = 2.62, p = 0.016). Strength asymmetry did not significantly influence the jump height, but was associated with lower ratio of CMJ/SJ height indicating that players without asymmetry have better jumping capacity in the terms of utilizing the stretch shortening cycle. CONCLUSIONS: Coaches should consider quadriceps strength as an important predictor of jumping capacity in top-level soccer players which is again related to sprint performance in soccer. Future studies are needed to evaluate the contributing impact of hamstring strength in this regard.